2015
DOI: 10.1155/2015/684794
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolites as Potential Biomarkers for Diagnosis of Knee Osteoarthritis

Abstract: Knee osteoarthritis (OA) is a highly prevalent chronic degenerative joint disease that mainly affects the elderly population. The aim of this study was to investigate serum signature metabolites as potential biomarkers for early diagnosis of knee OA. Global serum metabolic profiles of 40 patients with knee OA and 20 healthy controls (HC) were analyzed by ultra-performance liquid chromatography coupled to mass spectrometry. An OA-specific metabolic profile was established that can clearly discriminate patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 23 publications
5
34
0
Order By: Relevance
“…But epidemiological data supports that overall obese persons are more affected in knee OA 27,28,29 . In the present study incidence was more in normal BMI patients which was similar to Muraki S et al 30 Zhang Q et al 31 Vishal AA et al 32 & Radha MS et al 33 Out of 40 patients 22 (55%) patients were having sedentary lifestyle, 9 (22.5%) patients were having average lifestyle and 9 (22.5%) patients were laborers. Eminent Unani physicians have stated that excessive rest and lack of exercise may cause Wajaul-Mafasil 5,8,34 .…”
Section: Discussionsupporting
confidence: 85%
“…But epidemiological data supports that overall obese persons are more affected in knee OA 27,28,29 . In the present study incidence was more in normal BMI patients which was similar to Muraki S et al 30 Zhang Q et al 31 Vishal AA et al 32 & Radha MS et al 33 Out of 40 patients 22 (55%) patients were having sedentary lifestyle, 9 (22.5%) patients were having average lifestyle and 9 (22.5%) patients were laborers. Eminent Unani physicians have stated that excessive rest and lack of exercise may cause Wajaul-Mafasil 5,8,34 .…”
Section: Discussionsupporting
confidence: 85%
“…This reduction positively affects collagen cross-linking, since homocysteine has been shown to interfere with post-translational modifications of collagen through direct and indirect inhibition of lysyl oxidase as well as through down regulation of other genes involved in collagen cross-linking [28]. Indeed, Zhang et al recently reported elevated serum homocysteine levels in patients with severe OA compared to those with mild OA or healthy controls [29]. Secondly, although the exact role of silicon in bone and connective tissue health remains unclear, its involvement in collagen synthesis and/or stabilisation was recently put forward by Jugdaohsingh et al [30].…”
Section: Discussionmentioning
confidence: 99%
“…Obese individuals have a higher risk for OA compared to nonobese people [22]. Metabolites characteristics including energy metabolism and lipid and carbohydrate metabolism in the OA patients' synovial tissue cultures were significantly decreased compared with those with little or no evidence of the disease [23, 24]. Obesity increased mass and joint load and altered proinflammatory factor adipokines secretion, leading to the chronic low grade inflammatory status in joint tissues [25, 26].…”
Section: Discussionmentioning
confidence: 99%